Alcohol and nicotinic acetylcholine receptors - Jinsong Tang; Yanhui Liao (QScience Connect, 2013)
Background The frequent co-abuse of alcohol and tobacco may suggest that they share some common neurological mechanisms. For example, nicotine acts on Nicotinic acetylcholine receptors (nAChRs) in the brain to release dopamine to sustain addiction. Might nAChRs be entwined with alcohol? Objectives This review summarizes recent studies on the relationship between alcohol and nAChRs, including the role of nAChRs in molecular biological studies, genetic studies and pharmacological studies on alcohol, which indicate that nAChRs have been potently modulated by alcohol. Methods We performed a cross-referenced literature search on biological, genetic and pharmacological studies of alcohol and nAChRs. Results Molecular biological and genetic studies indicated that nAChR (genes) may be important in mediating alcohol intake, but we still lack substantial evidence about how it works. Pharmacological studies proved the correlation between nAChRs and alcohol intake, and the association between nicotine and alcohol at the nAChRs. The positive findings of varenicline (a partial agonist at the _4_2 nAChR, smoking-cessation pharmaceutical) treatment for alcoholism, provides a new insight for treating co-abuse of these two substances. >Conclusions Molecular biological, genetic and pharmacological studies of alcohol at the nAChR level, provide a new sight for preventing and treating the co-abuse of alcohol and nicotine. Given the important role of nAChRs in nicotine dependence, the interaction between alcohol and nAChRs would provide a new insight in finding effective pharmacological treatments, in decreasing or stopping alcohol consumption and cigarette smoking concurrently.